Le remploi des ivoires dans l’occident haut-médiéval (VIIe-XIe siècles) - Caillet, Jean-Pierre (Hortus Artium Medievalium, 2011)
Abstract The re-use of ivory items in the Western Early Middle Ages is the result of drastic shortage of raw material (the Muslims having control, then, of all supplying counters). So, Late Antique pieces might be re-employed without any change; but more often they underwent re-carving. First we have to deal with tablets, at the back of which lists of saints, bishops or donors are written. Sometimes too, a diptych becomes incorporated in a reliquary; and perhaps, some pyxids served for hosts stocking. But, from the 8th century onwards, the main use is for book binding ornamentation. Beyond this “utilitarian” character, re-uses of ivories should also be considered as references to the prestige of what had been created during Antiquity, or, for the Ottonians, to the prestige of pieces of Carolingian or Byzantine origin. So, regarding the five centuries here taken into account, the destinies of these items perfectly reveal the various valuations involved by the re-use phenomenon.